Senior secondary school chemistry students’ knowledge of climate change in the Niger Delta Region of Nigeria - Zudonu, Onisoman Chuks; Wagbara, Samuel Owundiwe; Ikwut, Emmanuel Friday; Iroro, Patricia E (Faculty of Natural and Applied Sciences Journal of Mathematics, and Science Education, 2024)
This work investigated the Knowledge of Chemistry Students on Climate Change in Senior Secondary Schools in the Niger Delta area of Nigeria. The study adopted a descriptive survey design. The sample of the study consists of five hundred and twenty (520) participants (223 males and 297 females) who were randomly selected from 50 senior secondary schools in the region. The instrument used for this study was titled Knowledge of Chemistry Students in Climate Change Structured Questionnaire in the Niger Delta area (KCSCCSQND). The items were structured on a 5-point Likert scale. The instrument consists of 30 items that address the three research questions. The instrument was face-validated and the reliability coefficient using the test-retest method was 0.81. Descriptive statistic of percentages was used to answer the research questions. It was established that chemistry students in the Niger Delta hold a good knowledge of climate change and the untoward effect of weather variation in the Niger Delta region. Some of the chemistry students in the Delta area remained neutral to ways and methods of mitigating temperature alteration and its effect in the Delta zone due to their incomplete knowledge of the art of weather change. Hence, recommendations were made to the Government and relevant stakeholders that there should be establishment of vital programmes to increase the awareness of climate change and effective methods to curtail its effect in the country and Niger Delta in particular.